2022
DOI: 10.1007/s10919-021-00395-x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Facial Self-Resemblance on Emotional Mimicry

Abstract: Social resemblance, like group membership or similar attitudes, increases the mimicry of the observed emotional facial display. In this study, we investigate whether facial self-resemblance (manipulated by computer morphing) modulates emotional mimicry in a similar manner. Participants watched dynamic expressions of faces that either did or did not resemble their own, while their facial muscle activity was measured using EMG. Additionally, after each presentation, respondents completed social evaluations of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 90 publications
(111 reference statements)
1
1
0
Order By: Relevance
“…Studies on crossmodal mimicry corroborate the latter assumption, showing that facial mimicry may occur in response to prosody 53 and body posture 54 . The evidence that mimicry depends on an affiliative goal fits with the social glue hypothesis, remarking on the dependency of mimicry on liking 55 , physical similarity 56 , and a cooperative goal 48 , as well as the increased mimicry occurrence for affiliative facial expressions compared to non-affiliative 57 . In response to the handful of studies that looked at and found evidence for the mimicry of negative emotional expressions 58-60 , Hess and Fischer argue that "antagonistic mimicry -the mimicry of antagonistic emotions -is not mimicry at all, but rather represents an emotional reaction to the expression of the other" 4 .…”
Section: Box 1 How Do We Mimicsupporting
confidence: 67%
“…Studies on crossmodal mimicry corroborate the latter assumption, showing that facial mimicry may occur in response to prosody 53 and body posture 54 . The evidence that mimicry depends on an affiliative goal fits with the social glue hypothesis, remarking on the dependency of mimicry on liking 55 , physical similarity 56 , and a cooperative goal 48 , as well as the increased mimicry occurrence for affiliative facial expressions compared to non-affiliative 57 . In response to the handful of studies that looked at and found evidence for the mimicry of negative emotional expressions 58-60 , Hess and Fischer argue that "antagonistic mimicry -the mimicry of antagonistic emotions -is not mimicry at all, but rather represents an emotional reaction to the expression of the other" 4 .…”
Section: Box 1 How Do We Mimicsupporting
confidence: 67%
“…Additionally, people mimic more those who are similar to them and with whom they would rather affiliate. For example, physically similar people are more likely to be mimicked than dissimilar people (Olszanowski et al, 2022), as are ingroup members rather than outgroup members (Bourgeois & Hess, 2008;Van der Schalk et al, 2011). Similarly, faces of individuals associated with communal traits indicating affiliative intentions are imitated more often than those without such traits (Wróbel et al, 2021).…”
mentioning
confidence: 99%